2018
DOI: 10.1111/ruso.12207
|View full text |Cite
|
Sign up to set email alerts
|

Women's Work? The Relationship between Farmwork and Gender Self‐Perception

Abstract: Women have long been involved in agricultural production, yet farming and ranching have been associated with masculinity and men. In recent years women have become more involved and more likely to take active and equal roles on farms and ranches and thus increasingly are doing tasks that have been associated with masculinity. Prior work indicates that women are perceived by others as more masculine when they do these tasks, but less work has focused on the association between women's involvement in farming and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…As expected, some work issues in agriculture remain strongly related to specific scientific communities. For example, the labor market, employment, and income are addressed mainly by agricultural economics (Pfeiffer et al 2009; Alvarez-Cuadrado and Poschke 2011), while division of labor by gender is addressed mainly by rural sociology (Melberg 2003;Smyth et al 2018). Our results indicate, however, that contemporary agricultural dynamics has renewed the entry point for discussing work issues, such as diversification of farmer activities (including off-farm work), and the increase in the number of hired workers, especially migrants.…”
Section: Major Current Issues Addressed By the Scientific Communitiesmentioning
confidence: 71%
“…As expected, some work issues in agriculture remain strongly related to specific scientific communities. For example, the labor market, employment, and income are addressed mainly by agricultural economics (Pfeiffer et al 2009; Alvarez-Cuadrado and Poschke 2011), while division of labor by gender is addressed mainly by rural sociology (Melberg 2003;Smyth et al 2018). Our results indicate, however, that contemporary agricultural dynamics has renewed the entry point for discussing work issues, such as diversification of farmer activities (including off-farm work), and the increase in the number of hired workers, especially migrants.…”
Section: Major Current Issues Addressed By the Scientific Communitiesmentioning
confidence: 71%
“…This study utilized cross-sectional data collected from a mail survey sent to women on cattle and wheat operations across the state of Washington in 2006 (more details can be found in Smyth et al, 2018). The survey contained questions based on early interviews and adaptation of the instruments of others who have surveyed women in agriculture.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Women who claim the farmer title struggle to be interpreted as farmers in their local and agricultural communities (Keller 2014). In addition, the label is infused with masculine connotations to the extent that women who call themselves farmers report higher self-perceptions of masculinity than women on farms who see themselves primarily as homemakers (Smyth, Swendener, and Kazyak 2018). Strikingly, the U.S. Census of Agriculture did not include gender on their survey until 1978, when it found that 5% of farms were operated by women (Hoppe and Korb 2013, iv).…”
Section: Women Farmers: Re-orienting Gender Relations On Farmsmentioning
confidence: 99%